A task scheduling algorithm for arbitrarily-connected processors with awareness of link contention - ALKAYA, ALİ FUAT; TOPCUOĞLU, HALUK RAHMİ (SPRINGER, 2006)
In this paper, we present a new task scheduling algorithm, called Contention-Aware Scheduling (CAS) algorithm, with the objective of delivering good quality of schedules in low running-time by considering contention on links of arbitrarily-connected, heterogeneous processors. The CAS algorithm schedules tasks on processors and messages on links by considering the earliest finish time attribute with the virtual cut-through (VCT) or the store- and-forward (SAF) switching. There are three types of CAS algorithm presented in this paper, which differ in ordering the messages from immediate predecessor tasks. As part of the experimental study, the performance of the CAS algorithm is compared with two well-known APN (arbitrary processor network) scheduling algorithms. Experiments on the results of the synthetic benchmarks and the task graphs of the well-known problems clearly show that our CAS algorithm outperforms the related work with respect to performance (given in normalized schedule length) and cost (given in running time) to generate output schedules.
Keywords: DAG scheduling; task graphs; link contention; heterogeneous systems; GENETIC ALGORITHM; SYSTEMS; PERFORMANCE